Sufism in Western contexts (Leiden ; Boston)
xi, 411 sayfa
Keywords: “Sufism in Western Contexts explores both historical trajectories and multiple contemporary manifestations of Islamic mystical movements, ideas, and practices in diverse European, North and South American countries, as well as in Australia – all traditionally non-Muslim regions of the “global West”. From early French and British colonial administrators who admired Persian poetry to nineteenth-century American transcendentalists, followed by South Asian and Middle Eastern immigrant Sufi guides and their movements, expansive and many-faceted expressions of Sufism such as its role in Western esotericism, female whirling dervishes and Rumi cafes, and new articulations in cyberspace, are traced and analyzed by international experts in the field“ --